Chinese Women's Acceptance of Intimate Partner Violence Against Women - Li, Carrie K. W. (Violence against women, 2023)
Few studies have empirically examined factors influencing attitudes toward acceptance of intimate partner violence (IPV), and no study has yet studied the topic in China. We empirically test the effects of attitudes toward gender roles and exposure to violence during childhood on the acceptance of IPV and the moderating effects of education and income on these relationships. Using survey data collected from 600 Chinese women from southern China, we found that education and income moderate the relationship between belief in gender equality and acceptance of IPV. The effect of exposure to parental physical violence on the acceptance of IPV is moderated by education.